2009
DOI: 10.1016/j.ultramic.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of high resolution protein structure by cryo-electron microscopy of vitreous sections

Abstract: We have quantitated the degree of structural preservation in cryo-sections of a vitrified biological specimen. Previous studies have used sections of periodic specimens to assess the resolution present, but preservation before sectioning was not assessed and so the damage due particularly to cutting was not clear. In this study large single crystals of lysozyme were vitrified and from these X-ray diffraction patterns extending to better than 2.1 Å were obtained. The crystals were high pressure frozen in 30% de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Improved resolution should be possible. Using lysozyme crystals, Sader et al (35) showed that vitreous cryosections retrieve structural information down to 7.9 Å, meaning that a resolution of <1 nm can be expected in the cellular context. The field of high-resolution membrane analysis is now largely open to further progress by the combination of high-resolution CEMOVIS and CET.…”
Section: Discussionmentioning
confidence: 99%
“…Improved resolution should be possible. Using lysozyme crystals, Sader et al (35) showed that vitreous cryosections retrieve structural information down to 7.9 Å, meaning that a resolution of <1 nm can be expected in the cellular context. The field of high-resolution membrane analysis is now largely open to further progress by the combination of high-resolution CEMOVIS and CET.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that large, tightly ordered macromolecular complexes, like the 80S ribosome, can withstand this specific type of mechanically induced deformation, because of its relatively small size (compared to the whole cell) and its structural order. In a similar study, it has been shown that electron diffraction patterns of high-pressure frozen vitreous cryo-sectioned lysozyme crystals can extend to 7.9 Å (Sader et al, 2009). Both studies indicate that after vitreous cryo-sectioning (and all associated sectioninduced artifacts) structural information can be retained up to the given resolution limit.…”
Section: Discussionmentioning
confidence: 79%
“…The methods used to maintain crystal quality while diffraction data are collected include sugar-embedding (e.g. using trehalose; Schebor et al, 2010), Paratone-N oil coverage (Hunter et al, 2014), vitrification (Sader et al, 2009), 'sandwich' enclosure (Coquelle et al, 2015) and wrapping in watertight graphene sheets (Wierman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%